Bioremediation Techniques for contaminated Land: Focusing on Land Contaminated by Petroleum Hydrocarbon Pollutants - Wahyu Dian Silviani (Indonesian Journal of Environmental Management and Sustainability, 2020)
Oil spills on land is one of major environmental issues. The spills have been known to affect not only environment but also human health. Certain bioremediation techniques, biostimulation, bioaugmentation, and land farming, have been widely applied to solve the problem. Approaches using these methods, over the years, have given varying result and rate of success. In this paper, advantages, disadvantages, and limitation of the techniques when applied will be discussed.